Evaluation of motor learning in predictable loading task using a force sense presentation device - Ota, Tetsuo; Kikuchi, Yui; Amiya, Ikumi; Ohno-Shosaku, Takako; Koike, Yasuharu; Yoneda, Mitsugu (Experimental brain research, 2022)
Neural circuits connecting the cerebellum with the cerebral cortex are important for both motor and cognitive functions. Therefore, assessment of cerebellar function is clinically important for patients with various motor and cognitive dysfunctions. Cerebellum-dependent motor learning has been studied using various tasks. The most widely used tasks are visuomotor adaptation tasks, in which subjects are required to make movements in two dimensions. Studies using simpler tasks of one-dimensional movement, which are easier for patients with motor problems to perform, have suggested that anticipatory responses in these tasks are useful to evaluate cerebellum-dependent motor control or motor learning. In this study, we examined whether the motor learning process can be evaluated in a simple loading task. Using space interface device for artificial reality (SPIDAR), a constant downward force was loaded to subjects’ hands in a predictable condition, and the vertical movement of the hand was recorded. The hand deflection from the initial position was displayed on a screen for visual feedback information. We examined effects of repeated loading task training (90 times) on hand movements, by analyzing a small upward movement just before loading (anticipatory response) and a large downward movement after loading in each trial. We found that the repeated training lowered the time constant of upward movement and reduced the amplitude and time-to-peak of downward movement. These training effects were maintained into the next day. Furthermore, we found that loading task training with eyes closed was also effective, which indicates that proprioceptive information is enough for improvement of performance.